Analysis of Chinese herbal compound preparations by ballpoint connector supported solvent microextraction and high-performance liquid chromatography with ultraviolet detection. Issue 1 (31st December 2021) - Zhang, Li-ping; Li, Zhuo-yi; Geng, Xiang; Zhang, Yi-fang; Tie, Dan; Chen, Xuan; Hu, Shuang; Xue, Xue
Abstract: Chinese herbal compound preparations are commonly composed of multiple traditional Chinese medicines (TCMs). The components of Chinese herbal compound preparation are complex, therefore, in this paper, ballpoint connector supported solvent microextraction (BC-SME) coupled with high-performance liquid chromatography with ultraviolet detection (HPLC/UV) is reported for the simultaneous extraction, enrichment and determination of the active flavonoids and anthraquinones with minimal waste production. The primary parameters affecting the performance were optimized, including the reuse of the ballpoint connector (BC), extraction solvent, pH of the sample solution, stirring rate, salt concentration, and extraction time. Under the optimal conditions, good linearities with r ≥ 0.9966 were obtained. The limits of detection (LODs) and quantitation (LOQs) were from 0.1 to 0.3 ng/mL and 0.4 to 0.9 ng/mL, respectively. The intra-day and inter-day relative standard deviations (RSDs) were less than 6.6% and the average recoveries were between 93.4% and 106.0%. Moreover, the analyte enrichment factors ( EF s) were from 63 to 391. The results showed the method was simple, economical, sensitive, and provided high enrichment and allowed the extraction of flavonoids and anthraquinones in Chinese herbal compound preparations.